Perancangan dan Implementasi Aplikasi Toko Koperasi Sekolah berbasis Website dengan Memanfaatkan Payment Gateway Midtrans (Studi Kasus: SMK Negeri Temayang) - Ayezha Halidar Putri Irwanda; Bayu Rahayudi; Dwija Wisnu Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Cooperatives at SMK Negeri Temayang are spaces that are usually used by students in conducting transactions between students and cooperative officers. Currently, the SMK Negerti Temayang cooperative serves students in making purchase transactions for food, beverages, and goods still using the conventional system. Problems that arise in making purchase transactions at cooperative stores during recess hours result in students and other visitors not being neatly arranged in queues and may be crowded when they are about to buy, making it difficult to process orders made at about the same time. In addition, it causes cooperative managers to experience obstacles and errors in summing the results of sales transactions in cooperative stores. The solution to this problem was designed and built a menu and goods ordering system, namely,